ESG and Commercial Sustainability: A Commercial Threat and Value Perspective (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Environmental, Social, and Governance(ESG) has come central to commercial strategy worldwide. However, ESG is a framework for business risk management and value preservation rather than philanthropy or activism. This chapter makes the case that ESG is not a moral requirement but rather a tool for lowering risk, safeguarding capital availability, and guaranteeing long-term business sustainability. by combining the concepts of fiscal threat pricing, agency proposition, legality proposition, and stakeholder proposition. This chapter make an attempt to explain how ESG capability reduces functional threat, imporve stakeholder trust, minimize cost of capital, and enhances companies value. Additionally, it looks at ESG challenges as valuation catalysts that lead to unusual returns and heightened perceptions of danger.. Further, it provids a corporate-focused interpretation of ESG issues that is relevant to directors, policymakers, and researchers.